Pre-islamic archaeology of Kuwait, Northeastern Arabia, Bahrain, Qatar, United Arab Emirates and Oman: a bibliography - Haerinck, Ernie; Stevens, Karel Guy (1985)
Keywords: Archéologie – Oman; Bibliographie – Oman

Pre-islamic archaeology of Kuwait, Northeastern Arabia, Bahrain, Qatar, United Arab Emirates and Oman: a bibliography. First supplement, 1985-1995 - Haerinck, Ernie; Stevens, Karel Guy (Peeters, 1996)
Keywords: Archéologie – Oman; Bibliographie – Oman

ببليوجرافيا في تاريخ عمان - فوزي, فاروق عمر (المورد, 1974)
The author treats briefly MSS and partial editions of Izkawī, Sirḥān b. Saʿīd: Kashf al-Ghumma al-jāmiʿ li-Akhbār al-Umma; Ibn Ruzayq: Tārīkh A’immat wa-Sādat ʿUmān; Sālimī, ʿAbdl. b. Ḥumayyid: Tuḥfat al-Aʿyān bi-Sīrat Ahl ʿUmān; [Ṣuḥārī], Abū ‘l-Mundhir Salma b. Muslim al- ʿAwtabī: Ansāb al-ʿArab. He mentions some other sources of Omani history, taken from Wilkinson 1972a, and gives a list of western secondary literature on Oman. This article is clearly the product of a first exploratory investigation into the history of Oman.
Place: العراق
Keywords: Bibliographie – Oman

التأليف والنشر في عُمان - الفلاحي, أحمد (عالم الكتب, 1983)
Place: السعودية
Keywords: Bibliographie – Oman

Guide to Omani theses in the English language, 1970-1997 - ʿĀmirī, Muḥammad b. Ḥamad al- (Sultan Qaboos University, 1998)
Keywords: Bibliographie – Oman

Oman and Southeastern Arabia. A bibliographic survey - Shannon, Michael Owen (G.K. Haal and Co., 1978)
Keywords: Bibliographie – Oman

Documentation on Oman - Pearson, J. (Journal of Oman Studies, 1983)
Keywords: Bibliographie – Oman

Bibliographie über das Sultanat Oman. Stand Juli 1980 - Düster, Joachim; Scholz, Fred (Deutsches Orient Institut, 1980)
Keywords: Bibliographie – Oman

Bio-bibliographical background to the crisis period in the Ibāḍī Imāmate of Oman - Wilkinson, John Craven (Arabian Studies, 1976)
Keywords: Bibliographie – Oman

Oman - Clements, Frank (Clio Press, 1981)
Keywords: Bibliographie – Oman